Financial objectives and satisfaction with life: A mixed-method study in surf lifestyle entrepreneurs - O’Neill, A.; Dias, Á.; Patuleia, M.; Pereira, L. (Social Sciences, 2022)
Tourism lifestyle entrepreneurs (TLEs) have introduced an innovation in business management based on the region, community, environmental sustainability, and extra financial factors. This type of entrepreneur allows the development of regions by attracting investment and presenting innovative products/services and is an important aid to the local economy. Based on the importance of TLEs, this study aims to explore factors influencing satisfaction with life as a key ingredient to attracting surf TLE. For this purpose, priority was given to obtaining primary data through a sequential approach of mixed methods, first with a quantitative study using survey data of 109 surf TLEs, followed by in-depth interviews. The results show that a good contact network and a strong link to a place influence satisfaction with life in a positive way. As a result, the moderating effect of financial objectives on these relationships alerts destination decision-makers about different entrepreneurial approaches regarding surf businessman attraction. This study makes an important contribution by providing empirical evidence regarding the ongoing discussion about financial vs. non-financial objectives for this type of entrepreneur, showing that both are important for their decision-making process. These results provide valuable insights for several industry stakeholders, namely funders (for grant approval), policymakers (alerting that these entrepreneurs should be addressed considering non-financial objectives), and entrepreneurs (alerting to goal definition patterns).